Validation of reported dentoalveolar relationships in the Swedish Quality Registry for Cleft Lip and Palate. (5th October 2019) - Pegelow, Marie; Klintö, Kristina; Stålhand, Gudrun; Lemberger, Mathias; Vesterbacka, Malin; Rizell, Sara; Chalien, Midia Najar; Björnström, Lena; Becker, Magnus; Lindberg, Marianne; Marcusson, Agneta; Karsten, Agneta
Summary: Objectives: The present study validated data that had been reported to the Swedish Quality Registry for Cleft Lip and Palate (CLP) under new requirements from 2016, when use of the 5-year-old (5YO) and the Modified Huddart and Bodenham (MHB) indices for rating occlusion in children born with unilateral CLP (UCLP) was introduced. Materials and methods: The sample included blinded study casts ( n = 97) and photos ( n = 4) of 5-year-old children who had been born with UCLP in 2009−2011 and were enrolled at one of six cleft centres in Sweden. Fourteen orthodontists from the centres assessed the patients ( n = 101) using the 5YO and the MHB indices. Median 5YO and MHB scores of the 14 assessments were compared with original registry data ( n = 61). Each centre devised code keys to protect the identities of their patients in the registry. Results: Interrater agreement among the 14 orthodontists was good for the 5YO index (quadratic-weighted kappa: 0.72−0.92) and the MHB index (intraclass correlation coefficient: 0.991−0.994). Comparisons of median 5YOs for each identifiable child with their registry data ( n = 61) found total agreement for 70.5 per cent. Comparisons between median MHBs and registry data showed very good or good agreement in 93.4 per cent of the cases. Limitations: Two teams lost their code keys, which reduced the sample to 61 patients. Conclusions: The dentoalveolar outcome data in the CLP registry was trustworthy. There was good agreement among the Swedish cleft teams assessing the 5YO and MHB indices in children born with UCLP at age 5 years.